Evolution of the 2015 Cotopaxi eruption revealed by combined geochemical and seismic observations - Hidalgo, Silvana; Battaglia, Jean; Arellano, Santiago; Sierra, Daniel; Bernard, Benjamin; Parra, René; Kelly, Peter; Dinger, Florian; Barrington, Charlotte; Samaniego, Pablo (Geochemistry, geophysics, geosystems, 2018)
Through integration of multiple data streams to monitor volcanic unrest scientists are able to make more robust eruption forecast and to obtain a more holistic interpretation of volcanic systems. We examined gas emission and gas geochemistry and seismic and petrologic data recorded during the 2015 unrest of Cotopaxi (Ecuador) in order to decipher the origin and temporal evolution of this eruption. Identification of families of similar seismic events and the use of seismic amplitude ratios reveals temporal changes in volcanic processes. SO2 (300 to 24,000 t/d), BrO/SO2 (5-10 × 10−5), SO2/HCl (5.8 ± 4.8 and 6.6 ± 3.0), and CO2/SO2 (0.6 to 2.1) measured throughout the eruption indicate a shallow magmatic source. Bulk ash and glass chemistry indicate a homogenous andesitic (SiO2 wt % = 56.94 ± 0.25) magma having undergone extensive S-exsolution and degassing during ascent. These data lead us to interpret this eruption as a magma intrusion and ascend to shallow levels. The intrusion progressively interacted with the hydrothermal system, boiled off water, and produced hydromagmatic explosions. A small volume of this intrusion continued to fragment and produced episodic ash emissions until it was sufficiently degassed and rheologically stiff. Based on the 470 kt of measured SO2 we estimate that 65.3 × 106 m3 of magma were required to supply the emitted gases. This volume exceeds the volume of erupted juvenile material by a factor of 50. This result emphasizes the importance of careful monitoring of Cotopaxi to identify the intrusion of a new batch of magma, which could rejuvenate the nonerupted material.